Histomorphology of Indian bee (Apis cerana indica Fab.) supplemented with probiotics - Akhila Pahee (Department of Agricultural Entomology, College of Agriculture, 2019)
The study entitled “Histomorphology of Indian bee (Apis cerana indica Fab.) supplemented with probiotics” was undertaken at College of Agriculture, Vellayani, Thiruvananthapuram during 2017- 19. The main objective was to assess the histomorphology of midgut of Indian bee’s (Apis cerana indica Fab.) suffering from various stressors (pathogens and insecticides) and, after being fed with probiotics. Purposive sampling was conducted at Thiruvananthapuram, Kollam, Pathanamthitta and Idukki districts for the present study. Twelve larvae (3 to 4 days old) each from naturally occurring feral colony, domesticated colonies which were fed with and without sugar syrup, naturally infected ones with bacterial brood disease as well as larvae fed with insecticide treated royal jelly (Thiamethoxam 25% WG) were collected and subjected to histomorphological evaluation. Also, the effect of probiotics on larvae under different stress conditions were also evaluated. The study mainly focused on the variations in the midgut histology of the larvae. The midgut of the honey bee larvae from feral colony had high epithelial integrity, well defined brush bordered microvilli which probably helps in the easy absorption of nutrients, prominent regenerative cells that is responsible for epithelial cell replacement and copious secretion of peritrophic membrane that are intented for the protection of the midgut from abrasive food particles, pathogen and toxins. The larvae of the colonies which were not fed with sugar also had similar histology. Histomorphological studies of honey bee larvae fed with sugar syrup, revealed the adverse effect of sugar on midgut cells viz., presence of vacuoles in the epithelium, absence of microvilli, reduced number of regenerative cells and uneven peritrophic membrane secretion. Studies on the midgut histomorphology of bacterial brood disease infected larvae indicated necrosis with picnotic or karyorrhectic nuclei, moderate to severely vacuolated cytoplasm, inconspicuous microvilli and distorted peritrophic membrane. Only occasional regenerative cells were apparent. The midgut epithelial cells of the larvae fed with insecticide, thiamethoxam 25% WG @ 0.05g L-1 exhibited only the presence of vacuoles of variable sizes. The midgut histomorphology of honey bee larvae treated with the probiotic, Darolac (1.25 x 109 cells of Lactobacillus acidophilus, L. rhamnosus, Bifidobacterium longum and Saccharomyces boulardi g -1 @ 1.2 g L-1 of water and sugar syrup) at weekly intervals for a period of four weeks was also evaluated. An increased cell activity which was indicated by the prominent aposematic secretion towards the gut lumen was observed in those larvae supplemented with probiotics when compared with that of the normal larvae from feral colony. Apart from these, enhanced integrity of the epithelial columnar cell, even distribution of microvilli and augmentation in the secretion of peritrophic membrane was also recorded. The present investigation revealed that the larvae fed with sugar syrup or those exposed to various stressors (disease and insecticide) had adverse effect on the midgut where they exhibited necrosis of epithelial cells, broken and unclear microvilli and distorted peritrophic membrane. Thus, the disruption of epithelial cells hindered the absorption of nutrients and water which led to the death of honey bee larvae. When probiotic (Darolac @ 1.2 g L-1) was supplemented to honey bee larvae under different stressors, it helped in mitigating the intensity of cell necrosis by restoration of regenerative cells and the larval health was found to be recovered which was indicated by the even distribution of microvilli.